'We will memorise our home': exploring settler colonialism as an interpretive framework for Kashmir. - Mushtaq, Samreen; Amin, Mudasir (Third World Quarterly, 2021)
In this article, we examine the practices of India's military occupation of Kashmir in the framework of settler colonialism to map its entrenched nature in sustaining control and countering the struggle for Azaadi (freedom). Post 5 August 2019, when the Indian state proceeded with a reading down of the laws that enabled Kashmir's permanent residents exclusive rights over land and jobs, scholars and activists noted it to be an advancement of India's settler logic of elimination. In this essay, we complicate its trajectory and trace these recent practices as part of long drawn processes including spatial, demographic and ecological manifestations that are now further deepening and expanding a matrix of control characteristic of such a project. The paper argues that while settler colonialism could be used as a crucial interpretive framework for Kashmir and make it legible for an international audience, the reliance on a future Indian-citizen-settler runs the risk of invisibilising the Indian armed forces already permanently stationed in Kashmir and occupying vast tracts of land. The settler colonial framework can be a useful concept for Kashmir when its shrewd combination of assimilationist and eliminationist tactics is placed within the framework of military occupation, rather than as a distinct alternative.